Pengaruh Intensitas Modal, Intensitas Persediaan dan Tingkat Hutang terhadap Tarif Pajak Efektif: Studi Empiris Pada Perusahaan Consumer Non-Cyclicals Tahun 2017-2021 - Sadewa, Prima; Safitry, Umi (Perwira Journal of Economics & Business, 2023)
This study aims to examine the effect of capital intensity, inventory intensity and debt levels on Effective Tax Rates. Empirical Studies of Non-Consumer Cycle Companies Listed on the Indonesia Stock Exchange in 2017-2021 period. The theory used in this research is agency theory. population in this case study were 114 non-consumer cycle companies listed on the Indonesian Stock Exchange Exchange. The sampling technique in this study was purposive sampling. So that a sample of 24 companies was obtained. The type of data used is secondary. The analysis technique used is panel data regression analysis with the help of the Eviews 12 program where the classical assumptions were testedfirst before testing the hypothesis using the t-test, f-test and coefficients determination.